Foliar Disease in Fresh-Market Tomato Grown in Differing Bed Strategies and Fungicide Spray Programs - Mills, Douglas J (Plant disease, 2002)
A 3-year field study in central Maryland evaluated foliar disease in fresh-market tomato grown using combinations of four bed strategies and three fungicide programs. Bed strategies included uncovered beds with or without a composted dairy manure amendment or beds covered with black polyethylene or hairy vetch mulch. Fungicide programs included no fungicide, weekly fungicide, or fungicide applications scheduled according to the TOMCAST disease predictor. In plots with hairy vetch-covered beds, early blight caused by Alternaria solani, Septoria leaf spot caused by Septoria lycopersici, and defoliation were lower versus uncovered beds each year. Early blight and defoliation were lower in beds covered with vetch versus polyethylene mulch in 2 of 3 years. Disease severity, defoliation, and marketable yield were similar for the weekly and TOMCAST fungicide programs, with 40 to 50% fewer sprays using TOMCAST. Marketable yield was similar among bed strategies except for higher yields in covered versus uncovered and unamended beds in a relatively wet year and lower yields in vetch versus polyethylene beds in a dry year